2022
DOI: 10.1021/acsnano.2c05150
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition Directed Assembly of Plasmonic Gap Nanostructures for Single-Molecule SERS

Abstract: Gold nanocubes (AuNCs) with tunable localized surface plasmon resonance properties are good candidates for plasmonic gap nanostructures (PGNs) with hot spots (areas with intense electric field localization). Nevertheless, it remains challenging to create shape-controllable nanogaps between AuNCs. Herein, we report a DNA origami directed pattern recognition strategy to assemble AuNCs into PGNs. By tuning the position and number of capture strands on the DNA origami template, different geometrical configurations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…Niu et al reported an interesting strategy to create shape-controllable nanogaps between Au nanocubes (AuNCs) using DNA origami (see Figure 34H). 509 Due to the anisotropic nature of the AuNCs, their vertices, edges, and faces allowed for the creation of richer configurations of nanogaps than isotropic spherical AuNPs, together with significantly enhanced electromagnetic fields in these nanogaps. By tuning the position and number of capture strands on the DNA origami, pattern recognition was enabled to assemble AuNCs in different geometrical configurations with nanoscale precision and shape-controllable gaps.…”
Section: Single-molecule Surface-enhanced Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Niu et al reported an interesting strategy to create shape-controllable nanogaps between Au nanocubes (AuNCs) using DNA origami (see Figure 34H). 509 Due to the anisotropic nature of the AuNCs, their vertices, edges, and faces allowed for the creation of richer configurations of nanogaps than isotropic spherical AuNPs, together with significantly enhanced electromagnetic fields in these nanogaps. By tuning the position and number of capture strands on the DNA origami, pattern recognition was enabled to assemble AuNCs in different geometrical configurations with nanoscale precision and shape-controllable gaps.…”
Section: Single-molecule Surface-enhanced Raman Spectroscopymentioning
confidence: 99%
“…(H) DNA origami-directed pattern recognition strategy to assemble AuNCs for single-molecule SERS. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Dna-origami-enabled Nanophotonicsmentioning
confidence: 99%
“…17 However, the regular SERS detection performed at colloidal nanoparticles and solid substrates always faces the challenge of precisely fabricating the plasmonic gaps down to subnanometer distance and detailed local nanostructures. 18 It is worth noting that aliphatic amino acid molecules usually possess low Raman scattering cross sections and low specific affinity to noble metal surfaces. As a consequence, it is challenging to capture them into the plasmonic gaps to directly obtain their own SERS signals, let alone to detect molecular chirality.…”
Section: Introductionmentioning
confidence: 99%
“…When molecules are located in these sub-nanometer plasmonic gap regions, rich chemical and structural information of the molecules is accessible, allowing for ultra-sensitive detection down to a single molecule . However, the regular SERS detection performed at colloidal nanoparticles and solid substrates always faces the challenge of precisely fabricating the plasmonic gaps down to sub-nanometer distance and detailed local nanostructures . It is worth noting that aliphatic amino acid molecules usually possess low Raman scattering cross sections and low specific affinity to noble metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] So far, a variety of methods have been reported to modulate the particles assembly, such as through modified molecular mediation, [8,9] electric, [10] magnetic, [11] light [12] or fluidic [13] field direction, and interfacial selfassembly, [14] as well as template induced assembly. [15][16][17] Among these strategies, template induced particles assembly has shown remarkable advantage for deterministic placement of large spectrum of materials from micro-to nanometer dimensions and efficient integration with substrates, showing great significance in fabricating advanced devices in the fields of optics, [18] electronics, [19] biodetection, [20] etc. Especially, template-induced multicomponents assembly, with promising potential in superior micro-/nanodevices with new functionalities by utilizing interparticle electromagnetic coupling or other synergistic effects, [21,22] have been witnessed with great progress in the past several years.…”
mentioning
confidence: 99%